Korean historical documents in Russian archives. Issue 1 (January 2018) - Toropov, Aleksandr
Abstract : The history of Russian-Korean relations dates back several centuries. The first documented mention of migrants from Korea to the Russian Far East is dated November 1863, when the head of Novgorod outpost notified the military governor of Primorsky Oblast of a request submitted to him by Korean peasants for authorization to settle on Russian territories. The following years witnessed an acceleration of Korean migration to Russia. However, these migrants faced many troubles because of their lack of knowledge of the language, laws and customs of the country that had given them shelter. More recently there was an inflow to the Russian Far East of political emigrants who established the foreign centre of their national liberation movement for Korean independence in Primorsky Oblast. Russian Koreans, alongside other nations of Russia, have followed a complicated historical path; this includes their adaptation within the Russian Empire, revolution, civil war, collectivization, industrialization and deportation to Central Asia in 1937. Documents kept in Russian archives enable both the tracing of the adaptation processes undergone by Korean families who voluntary left their home country to remain permanently in Russia and of the complicated path they followed to become an essential element of all the nations within Russia; at the same time, the documents also allow for an objective assessment of those events to be made.